Isolation of a Relatively Air‐Stable, Bulky Silyl‐Substituted, Neutral Silicon‐Centered Radical. Issue 25 (14th June 2019) - Holzner, Richard; Kaushansky, Alexander; Tumanskii, Boris; Frisch, Philipp; Linsenmann, Fabian; Inoue, Shigeyoshi
Abstract : The bulky supersilyl‐substituted ( t Bu3 Si) silicon‐centered radical1 was synthesized and fully characterized by single‐crystal X‐ray crystallography, cyclic voltammetry (CV), and EPR spectroscopy. With its extremely sterically encumbered radical center, 1 is stable in the solid state in air for 16 hours without showing signs of decomposition. Thus1 is the most robust trisilyl‐substituted silyl radical to date and a promising candidate for application as electrode material in organic radical batteries. Furthermore, it was found to be a strong dehalogenation reagent and therefore might find application in organic syntheses. Abstract : A fairly air‐stable silyl radical has been synthesized by introducing a bulky supersilyl group ( t Bu3 Si) to the radical center. This strong kinetic stabilization makes it an interesting candidate for application as electrode material in lithium‐free batteries.